Coordination dynamics of circulatory and respiratory rhythms during psychomotor drive reduction - ÇOTUK, HASAN BİROL (ELSEVIER, 2004)
A 0.15-Hz rhythm band in cutaneous blood oscillations in awake human subjects was studied in cardiovascular-respiratory time series of five subjects relaxing naively or practicing hypnoid relaxation (autogenic training, or AT). Time series analysis used nonlinear algorithms, time-frequency distribution (TFD), postevent scan (PES) method, and linear fast Fourier transform (FFT) algorithm. This 0.15-Hz rhythm band caused phase synchronization with respiration at 1:2, 1:1, and 2:1 integer number (n/m) ratios for extended periods. During wave epochs, the 0.15-Hz rhythm band was amplified, causing the 0.15-Hz rhythm band to also appear in interbeat intervals and arterial blood pressure fluctuations. If phase synchronization of the 0.15-Hz rhythm band with respiration was established at a 1:1 integer number ratio, it was maintained and resulted in consensualization of all cardiovascular-respiratory oscillations at this frequency. Simultaneous cardiovascular and respiratory oscillations at about 0.1 Hz did not affect the appearance of the 0.15-Hz rhythm band in the photoplethysmography (PPG) signal. Recent evidence suggests the emergence of the 0.15-Hz rhythm band and n/m phase synchronization to result from nonequilibrium phase transitions operational in the network of lower brainstern neurons and associated parasympathetic neuronal effectors. These findings corroborate our notion of the 0.15-Hz rhythm band as a marker of the trophotropic mode of operation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: cutaneous microcirculation; autogenic training; interbeat intervals; n/m phase synchronization; wavelet analysis; dynamic systems; HUMAN CUTANEOUS MICROVASCULATURE; SKIN BLOOD-FLOW; SYMPATHOVAGAL BALANCE; SPECTRAL-ANALYSIS; LASER-DOPPLER; PAINFUL STIMULATION; NERVOUS CONTROL; BRAIN-STEM; MICROCIRCULATION; OSCILLATIONS